Graft choice has no significant influence on the rate of return to sport at the preinjury level after revision anterior cruciate ligament reconstruction: a systematic review and meta-analysis. Issue 1 (15th December 2016) - Kay, J; Naji, L; de SA, D; Simunovic, N; Peterson, D; Samuelsson, K; Musahl, V; Ayeni, O R
Abstract : Importance: For an athlete undergoing anterior cruciate ligament (ACL) reconstruction, regardless of the level of play, often the most patient-important outcome is the ability to return to sport. Various graft types are currently being used in revision ACL reconstruction; however, it remains unclear how graft choice affects the ability of athletes to return to sporting activities. Objective: To evaluate the rate at which patients return to sport after revision ACL reconstruction based on the graft choice. Evidence review: The databases PubMed (MEDLINE), Ovid (MEDLINE) and EMBASE were searched from database inception until 18 March 2016 by 2 reviewers independently. The systematic electronic search yielded 2666 studies. Inclusion criteria were English-language studies investigating revision ACL surgery on humans of all ages participating in sports of all levels with reported return to sport outcomes for patients stratified by graft choice. Conference papers, book chapters, review articles and technical reports were excluded. Findings: 16 studies (n=944 patients) met the inclusion criteria for our analyses with a mean follow-up of 60.7 months (range: 12–1008 months). 1 study was of level II evidence, 2 were level III and 13 were level IV. A meta-analysis of proportions was used to combine the rate of return to preinjury level for each graft type using a random effects model. The pooled rate of return to preinjury sporting level was 67% (95% CI 62% to 72%; I 2 =14.64%) for patients with a bone-patellar-tendon bone autograft, 55% (95% CI 39% to 71%; I 2 =76.71%) for patients with a hamstring tendon autograft and 64% (95% CI 56% to 74%; I 2 =82.12%) for patients with allografts. Conclusions and relevance: Pooled estimates suggest no significant influence of graft choice on the rate of return to sport at the preinjury level after revision ACL reconstruction. However, there is a lack of high quality, prospective, comparative studies evaluating the rate of return to sport from which to derive definitive conclusions on the efficacy of different graft choices. Level of evidence: Level IV, systematic review of level II to IV studies.